The Effects of Administering the Bowel Management Program in the Treatment of Fecal Incontinence Among Children With Chronic Refractory Constipation - Mobina Taghva Nakhjiri; Nazila Shahmansouri; Fatemeh Khodaygani; Maryam Ghavami Adel (Journal of Family and Reproductive Health)
Objective: Constipation is a prevalent issue among children and is generally treatable with simple therapeutic approaches. However, a considerable proportion of these children experience severe constipation that necessitates more invasive treatments, including surgical interventions. This study is designed to examine the effects of administering the Bowel Management Program (BMP) in the treatment of fecal incontinence and soiling among children with chronic refractory constipation. Materials and methods: The research involved 24 patients who presented at the Children’s Medical Center exhibiting symptoms of functional constipation and fecal incontinence. Each patient was enrolled in the study after a thorough review of their medical history, a physical examination, and other paraclinical measurements like barium enema or rectal manometry, ruling out the organic causes of constipation. The bowel management program was subsequently established for these patients. Results: This study examined 24 children, including 14 girls (58.3%) and 10 boys (41.7%), with a mean (SD) age of 4.8 (1.2) years for the girls and 5.4 (1.2) years for the boys. The analysis revealed that there was no significant correlation between symptom duration and treatment duration in relation to gender, as indicated by a p-value greater than 0.05. Spearman's correlation test showed a significant relationship between the children’s age and their treatment duration (p˂0.001, r=0.54) and also between their age and their clinical symptom duration (p˂0.001, r=0.59). Conclusion: The results showed that the children’s age was significantly correlated with their treatment duration and clinical symptom duration. The bowel management program can be an effective treatment for overflow incontinence in children with chronic refractory constipation.